INCLUSION OF INTELLECTUAL PROPERTY TO THE ECONOMIC TURNOVER OF COMPANIES - Kazbekov Beket Kabdualievich; Zhasulan Dana Maratkyzy (Academic Journal of Physical and Chemical Sciences, 2020)
The results of intellectual activity, being personalized in the form of intellectual property, have specific properties that provide clear competitive advantages to the economy of any level of the organization. In modern society, the results of human intellectual activity are the direct productive force, along with the traditional factors of production-land, labor and capital. The creation, dissemination and use of innovations, increasing the role and scale of intellectual property development are the main factors in the formation of an innovative economy.Intellectual property affects the competitiveness of the sphere of activity, the region, the country, and also determines the speed of emergence of new products and technologies. Intellectual property may be included in the intangible assets of organizations. Intellectual property obtained under a contract or license and rights to it as part of intangible assets shall transfer its value (through depreciation) to the cost of products (works, services) in accordance with the norms of depreciation and useful life.